Effective landau-devonshire-type theory of phase transitions in ferroelectric thin films based on the tilley-zeks model - Chew, Khian Hooi; Chan, H.L.W.; Ishibashi, Y.; Shin, F.G. (2003)
A generalized thermodynamic theory (effective Landau-Devonshire-type theory) for ferroelectric thin films undergoing second order phase transition is developed within the framework of the Landau-Ginzburg theory via the concept of extrapolation length delta in the Tilley-Zeks model. The free energy of the Tilley-Zeks model for ferroelectric thin films is cast into a clearer and simpler form from the usual integral expression form using suitable order parameters. The target coefficients A and B for the second order and fourth order terms, respectively, of the free energy ate expressed as a function of temperature, film thickness, extrapolation length and other physical parameters. The intrinsic effects of surface on the order of phase transitions are discussed analytically with an emphasis on asymmetric films.